Idealism and Utilitarianism in Internationalization of Higher Education - Chao Jr., Roger Y (International Higher Education, 2014)
This article argues for a holistic view of internationalization of higher education. Its two extremes of idealism and utilitarianism are presented as a guide to the multiple meanings and functions of internationalization of higher education within a changing world order.